Time-Effect of Donor and Recipient Characteristics on Graft Survival after Kidney Transplantation - Yang, Jingyan; Sardo Molmenti, Christine L.; Cagliani, Joaquin; Datta, Harish; Grodstein, Elliot; Rasul, Rehana; Rilo, Horacio; Teperman, Lewis W.; Molmenti, Ernesto P. (International Journal of Angiology, 2019)
The kidney allocation system (KAS) is based on quality-based “longevity matching” strategies that provide only a momentary snapshot of expected outcomes at the time of transplantation. The purpose of our study was to define on a continuous timeline the relative and mutual interactions of donor and recipient characteristics on graft survival.Total 39,108 subjects who underwent kidney transplant between October 25, 1999 and January 1, 2007 were identified in the United Network for Organ Sharing dataset. Our primary outcome was graft survival. Time-dependent receiver operating characteristic (ROC) curves and area under time-dependent ROC curve (AUC) were used to compare the predictive ability of the two allocation systems.During the first year after transplantation, both donor and recipient models showed identical relevance. From the first to the sixth years, although the two ROC curves were nearly identical, the donor model outweighed the recipient model. Both models intersected again at the sixth year. From that time onward, the ROC curve for recipient characteristics model predominated over the ROC curve for donor characteristics model. The predictive value of the recipient model (AUC = 0.752) was greater than that of the donor model (AUC = 0.673)We hope that this model will provide additional guidance and risk stratification to further optimize organ allocation based on the dynamic interaction of both donor and recipient characteristics over time.
Keywords: renal transplantation; kidney transplantation; KAS; UNOS; graft survival; organ procurement; recipient characteristics